Responsible management education : some voices from Asia - Swamy, Ranjini; Swamy, Ranjini (Principles for responsible management education collection., 2017)
Asia is home to a very large number of business schools. This edited collection emerged from the need to know about how business schools in Asia are inculcating Responsible Management. The book describes how some Asian business schools are incorporating ethics, social responsibility, and sustainability into their curricular and extra-curricular activities. It identifies the challenges faced in providing such education and the implications thereof. In the process it captures the unique flavor of Asian business schools. Data for the book was sourced from the workshop proceedings of the 6th PRME Asia Forum held in Goa, India in November 2015 and from case studies submitted before the Forum. The Workshop sessions were a demonstration-cum-discussion about the design and conduct of some courses on responsible management. The sessions were led by faculty members from (a) public autonomous institutes such as the Indian Institute of Management, Ahmedabad; (b) private autonomous institutes such as XLRI, Jamshedpur and MDI, Gurgaon; and (c) university departments such as The School of Economics and Management at Tsinghua University in China. Some of the case studies detail the curricular interventions introduced by some business schools to inculcate responsible management. Others share the experiences of faculty members in designing and conducting specific courses/modules on responsible management, the challenges experienced in inculcating responsible management and responses. The authors are faculty members/administrators representing the Indira School of Business Studies, Pune, India; the Hang Seng Management College, Hong Kong; the Colegio de San Juan de Letran Calamba, Philippines; the Indian Institute of Management, Indore, India; the KIIT School of Rural Management, Orissa, India; and the Department of Management Studies at a University in western India. Together the workshop proceedings and the case studies suggest that the sampled Asian business schools have introduced courses/modules on responsible management. However, few appear to have made responsible management a central part of business school strategy. There is need to develop a different worldview of education, one that focuses on the wellbeing of the planet and people, rather than the wellbeing of business alone. Support from other stakeholders is critical for this to occur. Additionally, faculty members require training and encouragement to integrate responsible management in their research agendas and courses.